The Importance of the Owner / Manager’s Profile in Accessing Banking Credit for SMES in the Trade / Distribution Branch in the Context Of Information Asymmetry: (L’importance Du Profil Du Proprietaire/Dirigeant Dans L’acces Au Credit Bancaire Des Pme De La Branche Commerce/Distribution En Contexte D’asymetrie D’information) (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of this article is to examine the impact of the various dimensions of the owner / manager profile on access to bank credit for Cameroonian SMEs working in the trade / distribution subsector. The results of the estimates carried out on a convenience sample of 93 SMEs / CDs highlight three main explanatory variables for access to bank credit, including the age of the owner / manager, his level of education and his relationship network intensity. Thus, owners / managers of SMEs/CDs aged 40 and over, with a high school education and a high network intensity are more likely to access the amount of credit requested. Therefore, promoters of SMEs / CDs would be better off establishing links with bankers, suppliers of goods or even associations in order to increase their chance of accessing the amount of credit requested.